The prevalence of chronic obstructive pulmonary disease in Elazig, Eastern Turkey - Deveci, Figen; Deveci, S. Erhan; Turkoglu, Suat; Turgut, Teyfik; Kirkil, Gamze; Rahman, Suheyla; Muz, M. Hamdi (Elsevier, 2011)
Background: To investigate the prevalence of Chronic Obstructive Pulmonary Disease (COPD) in the urban and rural areas of the Elazig Region of Turkey. Methods: A questionnaire was conducted and spirometric measurements were made, based on the BOLD protocol. A total of 1270 individuals, over 18 years of age, were included in the study, comprising 610 individuals from the city center and 660 from the rural area. The questionnaire included demographics, symptoms and possible risk factors. The description and staging of COPD were in accordance with GOLD (Global Initiative for Chronic Obstructive Lung Disease). Results: Of the 1270 cases, 1206 (94.9%) were able to complete the questionnaire and undergo spirometric analysis. Of these 1206 cases, 1188 (98.5%) were used in the final assessment; the remainder were excluded due to errors in the spirometric analysis. Of the cases included in the study, 43.2% (25.9% female; 56.7% male) were current smokers. The prevalence of COPD at >= 18 years old was 4.5% (female 2.5%; male 6%); the prevalence at >= 45 years old was 11.5% (female 5.9%; male 15.1%). The majority of the COPD cases were at stages I and II (22.6% and 66%, respectively). The prevalence of COPD was higher among current and former smokers (5.8%) than non-smokers (2.8%). In general, the risk factors for COPD were found to be age, male gender, smoking, living in a rural area, and low income. Conclusions: The prevalence of COPD in Elazig, Turkey was highest among the elderly and smokers, and constituted primarily stages I and II of the disease. (C) 2010 European Federation of Internal Medicine. Published by Elsevier B.V. All rights reserved.
Keywords: Chronic obstructive pulmonary disease; Prevalence; Risk factors